MEMBANGUN NATUNA SEBAGAI DESTINASI EKOWISATA DEVELOPING NATUNA AS ECOTOURISM DESTINATION - Hardini, Widi; Tyas Rosani Sri Harnanti (JURNAL MEKAR, 2022)
ABSTRACT Ecotourism is the whole of  activities that is responsible for maintaining the conservation and environmental aspect. These activity also involves the local communities to get some benefit. The research is to determine some potential objects and attraction in Natuna that can be develop for supporting ecotourism development program. This is also to elaborate the social community aspect and their  readiness to accept the tourist. Data obtain from the direct observation, interview, survey, and literature also secondary  data from the regency source. The data analyzed by using descriptive analysis technique. The result show that Natuna have some potential ecotourism attractions from the nature, culture and also social. Natuna need to develop and to supervise the local resources such as the hotel and tourism workers, the community and to support some potential resources like culinary traditional food and handicraft to support ecotourism development. To reach the goal, stakeholder must play the role and support to the local community